Body scan or loving kindness? Effects of two brief, short-term, self-administered mindfulness intervention on subjective wellbeing - Kang, Natalie Qian Yi (2017)
With increasing empirical attention on mindfulness as a way of improving wellbeing, there is a need to develop empirically-based interventions to aid in this pursuit. Furthermore, as traditional mindfulness practices typically last 1.5-2 hours and span 6-8 weeks, the feasibility of these interventions for general public usage would be increased if interventions were brief in duration, self-administered, and had been tested in samples that typically face high levels of daily stressors. Objectives. The study sought to evaluate whether two brief, short-term, self-administered mindfulness practices would reap similar benefits for subjective wellbeing. Pilot Study. A pilot study was conducted on 25 participants to test the effectiveness of the loving kindness and body scan mindfulness practices. Based on the findings from the pilot study, changes were made to improve the mindfulness practices, and incorporated within the two main studies. Study 1. One hundred and thirty-four undergraduates were randomly assigned to either the loving kindness, body scan, or control condition. Participants in both mindfulness conditions saw improvements in life satisfaction, basic needs satisfaction, self-compassion, and perceived ability to handle stress; and reduced levels of burnout and perceived stress. Study 2. Sixty-eight helping professionals were randomly assigned to either loving kindness or body scan mindfulness condition. Paired sample t-tests revealed similar results to Study 1; participants in both mindfulness conditions saw improvements in well-being, need satisfaction, and other stress and coping outcomes. Discussion. The findings suggest that both brief, short-term, self-administered loving kindness and body scan mindfulness practice are efficacious in improving one’s wellbeing. Theoretical and practical implications, limitations and future recommendations are discussed.